Infection of Upper Punctum and Canaliculi Caused by Actinomyces - Jamal Mughal, Akhtar Jamal Khan (Pakistan Journal of Ophthalmology, 2009)
Purpose: The clinical and microbiological findings in a chronic case of lacrimal canaliculitis due to Actinomyces are described. Material and Methods: A 55-year-old woman presented with a one year history of intermittent conjunctivitis associated with medial canthal swelling, pain and discharge from her right eye. Topical and oral treatment failed to respond, gram staining was carried out and surgical exploration was done. Results: Canaliculitis due to Actinomyces was diagnosed on the bases of clinical and laboratory findings. Canaliculotomy was carried out with fine needle of high frequency radio wave cautery of that area to minimize the chance of recurrence. Patient was completely asymptomatic after three moth follow up. Conclusion: Gram staining is a simple cheap and affordable method. It should be performed to identify the causative organism. Once diagnoses confirmed surgical exploration is the treatment of choice.